The Urgency of Patriotism in Maintaining the Unity in the Republic of Indonesia in the Perspective of Maslahah - Zezen Zainul Ali (Institut Agama Islam Negeri Palangka Raya, 2021)
Patriotism is the willingness of a citizen to protect the country to maintain national unity. Love for the homeland or patriotism often creates pros and cons in its interpretation. Then, it needs to raise awareness as a step to prevent conflicts that arise and consequently cause divisions within the country. The emergence of interpretations between Patriotism and religion that they cannot be combined, so they have willing to change the state ideology to other ideology, such as khilafah ideology through the emergence of radicalism, extremism, and separatism groups. The research was a literature review using literature data from related books and articles. Data analysis used a qualitative analysis. This study was expected to become a scientific treasure and be practiced in the life of the nation and state. Patriotism explicitly does not available stated in either the Qur'an or Hadith. However, in principle, Islamic law will always answer the problems to provide benefits for mankind, which is the maslahah. Having a love for the homeland is mubah (permitted), but it may switch to be mandatory during emergencies and conditions. This attitude of love for the homeland is in the condition of daruriyah.